Evaluation of Environmental Radiation Exposure and Algorithms for Determining the Occupational Effective Dose During 99mTc-MDP Bone Scintigraphy: A Comprehensive Analysis - Suphalak Khamruang Marshall; Awatif Hayeeabdunromae; Nadia Noomad; Wanita Durawee; Nantakorn Sirieak; Pornchanok Karnkorn; Virunyupa Keawtong (Applied Sciences)
This study evaluated the occupational exposure of radiopharmacists, nurses, radiological technologists, and radiological technologist assistants involved in 99mTc-MDP bone scintigraphy procedures. Actual occupational effective doses for individual staff needed ascertaining. An environmental radiation exposure audit revealed all nuclear medicine areas were compliant with ICRP and IAEA guidelines. To ascertain individual doses, they were recorded by OSL badges. The highest exposure was to the radiopharmacists, Hp(0.07) 2.19 µSv during radiolabeling. The nurse administering 99mTc-MDP recorded a dose of 0.27 µSv at Hp(0.07), 26.01% of the total occupational effective dose. The radiological technologist and assistant receive 73.05% of the total effective dose. However, the highest effective dose was received by the technologist assistant positioning patients for SPECT/CT scans, with an effective dose of 32.03 µSv. Single and double dosimetry effective dose estimate algorithms were evaluated, resulting in the double dosimetry being more accurate. The Padovani et al. algorithm was found to most closely align with 99mTc-MDP actual effective dose values (p > 0.05), thereby validating the measurement methods used in this study. The research offers benchmark environmental exposure and effective doses applicable in audits and the continuous effort to enhance radiation safety for personnel during 99mTc-MDP bone scintigraphy.